RESULTS OF PALEOTECTONIC AND STRUCTURAL-THERMO-ATMOGEOCHEMICAL RESEARCHES IN CONNECTION WITH OIL AND GAS POTENTIAL OF SKOROBAGATKOVSKA AREA, DNIEPER-DONETS DEPRESSION - Oliynyk, O.P.; Bozhezha, D.M.; Malychev, O.M. (Institute of Geological Sciences, NAS of Ukraine, 2017)
Skorobagatkovske oil and gas condensate deposit (the central part of the Dnieper-Donets Depression) corresponds to the complicated salt crypto-diapir structure. Prospects of deposit are associated with the Permian-Carboniferous, middle and Lower Carboniferous and Devonian oil-saturated layers. In order to clarify the expected horizons of hydrocarbons, comparison of the results of paleotectonic (isopach maps) and structural-thermal-atmo-geochemical researches (STAGR) (maps of temperature indicators, radon and butane contents in the subsoil air) was carried out. It was determined that the spatial distribution of promising locations coincides, however results of STAGR must be considered as more detailed in consequence of the areal measurements methods. Integrated use of both methods will increase the efficiency of exploration works.